Comparative analysis of chlorophyll and carotenoid pigments content of arugula (Eruca sativa) and lettuce (Lactuca sativa) leaves - Dumbrava Delia Gabriela (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
The aim of this study was to analyze the chlorophyll and carotenoids content of fresh arugula (Eruca sativa, Ruca variety) and lettuce (Lactuca sativa, Marilena variety) leaves from the Romanian market. The pigments concentration in the analyzed samples was determined by a spectrophotometric method. In both analyzed samples, chlorophyll "a" predominates to chlorophyll "b". The highest content of chlorophyll pigments was found in leaves of arugula: 31.47 mg/g, while in the lettuce leaves was found a concentration of 27.14.Arugulaleavesare alsothe richestincarotenoids (245.50 µg/g).